Ethical considerations at the intersection of climate change and reproductive justice: directions from green criminology - Haley, Sarah (Critical criminology, 2022)
This paper explores the relationship between climate change and reproductive injustice. It does so by highlighting several ethical concerns that warrant public policy attention at the intersection of full bodily autonomy and the transition to a carbon neutral economy. In Section one, the climate change science literature addressing the health and social harm disparities for low-income communities is summarized. This summary emphasizes the effects of this harm for poor women and girls of color. In Section two, the jurisprudential history regarding full bodily autonomy and reproductive justice is presented. This recounting draws attention to the historical legacy of inequality based on race, gender, and class. In Section three, the ethical implications of climate change are presented and discussed through the analytical lens of green criminology and reproductive justice. These implications include a feminist reclaiming of full bodily autonomy for poor women and girls of color, given the health and social inequalities they disproportionately experience.